Motivation of Service Sector Work: A Demographic Comparison - Kumar, S (2012)
The research that has been conducted aims at studying the motivation of employees that work in the fast food industry of the UK market. The interesting angle of the research is the comparison that it builds amongst the various employee cultures who are serving in the fast food segment. There are various dimensions for which the motivation of employees is measured. These variables are all the factors which are chosen to see their effect on their motivation levels. For the measurement of the motivation amongst the various employee cultures, the quantitative analysis has been conducted where more than 300 questionnaires have been used for the purpose of the exploration. SPSS has been used for the purpose of the analysis which is a very effective and accurate tool for going about the quantitative analysis in the research. It was a journey of great deal of learning, with interesting results, that allowed me to narrate various set of recommendations for the management of the fast food industry along with the conclusive argument leading to the limitations of the research.